Internationalization project of tulea´s tourism unit top - an in-depth market analysis of Germany - Ehmer, Benedikt (2024)
Small tourism businesses often internationalize through global Online Travel Agencies (OTAs). As OTAs exert price pressure, premium offers may seek independent internationalization. This project applies such an independent approach to a real premium short-term rental property. The systematic international market selection (IMS) process reveals affluent German families as the optimal target segment. Given the company’s resource constraints, Germany-specific, villa focused OTAs are identified as the optimal entry mode. Using the managers’ insights, a financial model is constructed that accounts for eventually increasing direct sales. Based on this model, the authors must conclude that the property will likely become a liability.